Caldera Collapse vs Volcanic Uplift - Avdis , Vaios (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
Despite the findings in Akrotiri that indicate its historical use as a harbor despite its current elevation of 300m, geologists argue that multiple caldera collapses occurred. Santorini has attracted the attention of both geoscientists and archaeologists. However, geoscientists have largely overlooked the presence of numerous high-angle faults with small dip-slip displacement and the formation of domes caused by these faults. The discovery of the buried town of Akrotiri, with its well-preserved buildings and artifacts, by archaeologists, along with the destruction of the flourishing Minoan civilization and Knossos in Crete during the same era, has generated significant interest. Plato's "Dialogues" discussing the catastrophe of Atlantis on the island is also relevant. However, the initial interpretation of the fall of huge areas in Santorini and the association with the legend of Atlantis by archaeologists, such as Galanopoulos in 1957, miscalculated the amount of volcanic ejecta and misinterpreted the features on the caldera walls. As an experienced field geologist, I argue that the topography of Santorini is mainly the result of faulting rather than erosion or volcanism. The slopes of Thira-Thiresia formed fold-like structures, and there was no caldera collapse.